Remoção biológica de fósforo utilizando sistemas de RBS no tratamento de águas residuárias domésticas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
According to the National Sanitation Information System - SNIS (2016), of all the sewage produced in Brazil, only 40.8% is subjected to some type of treatment, the other almost 60% is released in natura into the bodies of water. water, causing major environmental impacts; such as eutrophication, the proliferation of macro and micro vectors and, consequently, public and economic health problems. With regard to the treatment of domestic sewage, it is currently possible to carry it out through different types of reactor types. Among the proposals there are reactors with aerobic and anaerobic stages separated physically and temporally in a single reactor called Sequential Batch Reactors-RBS. Therefore, the present study aimed to evaluate a biological removal of phosphorus, using Sequential Batch Reactors with suspended biomass. For this, the treatment system was designed and built in cylindrical acrylic material, with a total height of 98.8 cm and a diameter of 10 cm, a useful volume of 5.853 liters, working with Hydraulic Detention Time (TDH) 1.43 days and Cell Retention Time (CRT) 3 days, alternating anaerobic and aerobic phases with a low concentration of dissolved oxygen (0.5 to 1.2 mgO2.L-1). Monitoring of physical and chemical parameters was carried out to verify the performance of the system. In the treatment, the efficiency of removal of organic matter in the form of COD (mgO₂.L¯¹) of 90.7% was verified in relation to the raw sewage. The system also removes approximately 76% of the phosphorus. When analyzing the fractions of solids in the treatment, the values of removal of total suspended solids are obtained with removal efficiency of 40% and 76% of volatile suspended solids, low values. The system also removed nitrogenous material, produced in the final effluent as average means, 2.89 mgN-NH₄⁺.L-¹; 0.097 mgNO₂¯.L-¹ and 0.63 mgNO₃¯.L-¹, ammoniacal nitrogen, nitrite and nitrate, respectively not final effluent from the system. Therefore, it is observed the general way, the physical and chemical parameters during the monitoring of the experimental system indicated good performance during the research, treating domestic sewage, producing effluents within the standards of elaborations defined in the environmental legislation, mainly in what concerns remove organic matter removal and phosphorus removal.
Keywords: Reator aeróbio; Matéria orgânica; Lodos ativados; CNPQ:: ENGENHARIAS